Selective Michael-type addition of a D-glucuronic acid derivative in the synthesis of model substances for uronic acid containing polysaccharides (eXPRESS Polymer Letters, 2008)
A flexible protocol for the preparation of model substances for uronic acid containing polysaccharides is presented. We have synthesized a D-glucuronic acid derivative which is designed so that it easily can be conjugated with different structures and architectures by selective Michael-type addition. By successful coupling of the glucuronic acid derivative to polyethylene glycol with high degree of conversion, products were obtained that were easily characterized and which resembled polysaccharides in terms of solubility and purification methods that could be employed. The model substance can potentially be used to facilitate optimization of low-degree modification reactions of high molecular weight D-glucuronic acid containing polysaccharides.